(3ebGeGJ aj GdfhGOQs
(3ChdgG (B:s
(3cGfhG eJhGOOjf Ydi TQH gPg GdVjY, aYGO Edi QCi CHjg s
(3BNQgG (B:s
(3eHJhQ BNQ GdehLhO efgG Ke JaGfh ai MHgG hYege HYHGOJgG caQkG haSGkO s
(3GdehLhO efgG ef U (B74 - 224s
(3HgG fXGe GdJYbjHIs
(3HHYV ChQGbgG JbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B90 s
Keywords: (3GdCOHs